The Impact on Obstetric and Perinatal Outcomes in Term Infants Following the Introduction of a Color-coded, Hierarchical Cardiotocography Classification System: A Retrospective Noninferiority Study. Issue 1 (22nd March 2023) - Willis, M.; Dunn, L.; Okano, S.; Janssens, S.; Kumar, S.
Abstract : ( Aust N Z J Obstet Gynaecol . 2022;62:370–375) The effectiveness of continuous cardiotocograph (CTG) monitoring relies on the accurate interpretation of the fetal heart rate (FHR) tracing, taken together with all available clinical information, and followed by appropriate clinical responses. CTG interpretation is dependent on the observations of the obstetrical team and subject to bias. Staff training and consistent, standardized FHR interpretation may help to improve the effectiveness of CTG monitoring. The Royal Australian and New Zealand College of Obstetricians and Gynaecologists' (RANZCOG) Intrapartum Fetal Surveillance recommends a CTG classification system using prose that defines fetal compromise as low, unlikely, maybe, or likely. A new color-coded system, the Queensland Clinical Guidelines (QCG), complements this prose-system, by using green, blue, yellow, and red to define fetal compromise, and recommends appropriate actions in response to each CTG category. The aim of this study was to assess the effectiveness of the color-coded CTG classification system on pregnancy outcomes before and after implementation.